August Dvorak (1894-1975): Early expressions of applied behavior analysis and precision teaching - Joyce, Bonnie (1988)
August Dvorak is best known for his development of the Dvorak keyboard. However, Dvorak also adapted and applied many behavioral and scientific management techniques to the field of education. Taken collectively, these techniques are representative of many of the procedures currently used in applied behavior analysis, in general, and especially in precision teaching. The failure to consider Dvorak's instructional methods may explain some of the discrepant findings in studies which compare the efficiency of the Dvorak to the standard keyboard. This article presents a brief background on the development of the standard (QWERTY) and Dvorak keyboards, describes parallels between Dvorak's teaching procedures and those used in precision teaching, reviews some of the comparative research on the Dvorak keyboard, and suggests some implications for further research in applying the principles of behavior analysis.